Strategies used for State Based Software Testing: A Review - Maiduli, Sanjay (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*278.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90306);" role="presentation">Testing is one of the most important means to validate the correctness systems, a state based testing is based on <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*292.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885808);" role="presentation">state machine, a state based testing approach allows for reuse of the test cases designed for the base program and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*305.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922825);" role="presentation">is therefore suitable for automatic generation of test cases (Binder, 2000). This paper is the review of strategies <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*318.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922218);" role="presentation">for state based software testing such as Round Trip Path (RTPT) tests and Sneak Path testing and comparison <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*331.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885308);" role="presentation">between two strategies used.